Hybrid CMOS Single-Electron-Transistor Device and Circuit Modeling. - Mahapatra, Santanu (Integrated Microsystems., 2006)
CMOS (complementary metal oxide semiconductor) is a widely accepted and utilized technology among electrical engineers involved with circuit design. SET (single electron transistor) technology has recently gained significant attention, because it can be combined with CMOSs to improve overall performance of integrated circuits -- reducing power consumption and achieving greater functionality. This cutting-edge resource provides professionals with the conceptual framework and specific strategies for CMSO-SET hybrid circuit design. The book offers a thorough understanding of the pros and cons of.